Plural Suffixation Skills in Developmental Language Disorders: A Preliminary Investigation From Bilectal Cypriot-Greek-Speaking Children With DLD - Petinou, Kakia; Giannikas, Christina N.; Papastefanou, Theodora; Hadjigeorgiou, Lia; Stamelou, Ioanna (My University, 2023)
Young children are known to make significant progress in learning their native language during the first 4 years of their life. Nonetheless, delays or differences in patterns of language acquisition can be cautiously determined and be sensitive indicators of developmental issues. The current paper displays an investigation that examines plural suffixation skills in preschool bilectal Cypriot-Greek (CG)-speaking children with developmental language disorder (DLD) as compared with their age-matched typically developing peers. Predictions have been made based on the Interpretability Hypothesis (IH) theoretical context postulating that grammatical features (inflections for Tense and Case Features) will be differentially affected in DLD depending on the phonological saliency inherent to specific inflection typology. Developmental language disorder diagnosis was based on exclusionary criteria and on clinical markers based on the language samples analyzed for grammatical errors, including the omission of articles in obligatory contexts, clitic misplacement, incorrect suffixation of plural targets, agreement errors, omission of negation, and reduced Mean Length of Utterance in Words (MLUw). A non-real-word experimental paradigm was used to test subject performance of plural suffixation. Findings revealed that plural suffixation difficulty was not an all-or-none phenomenon. Both erroneous and correct responses were identified during both experimental tasks. In addition, errors were observed in both groups of preschool children; nonetheless, the proportion of errors was recorded to be higher in the DLD group. © Hammill Institute on Disabilities 2023.
Keywords: Developmental language disorder; Plural suffixes; Cypriot Greek